Fiscal Decentralization in Croatia Fiskalna Decentralizacija u Hrvatskoj (Other Financial Sector Study, 2022)
The problems in Croatia's fiscal decentralization system have long been recognized. The fragmented territorial-administrative structure, fiscal decentralization efforts with insufficient fiscal autonomy, inconsistent public service standards, unbalanced sources of revenue, and doubts about the introduction of real estate taxes are just some of the concerns. However, there is often no consensus on the possible ways to address them. Compounding the problem is the fact that the recent and still ongoing tax reform, due to its tax relief element, has created the need to compensate subnational governments for the losses of revenues. The COVID-19 pandemic has increased the significance of these issues as the lockdown measures have had a strong negative impact on the existing revenue sources, such as personal income taxes (PITs), of many local and regional government units (LRGUs).